Enhancing Business Communication Skills: An Action Research - Khamis, Norazah; Wahi, Wahiza (International Journal of Asian Social Science, 2021)
This collaborative action research involving a lecturer and a student researcher intended to enhance a group of final-year students’ business communication skills to prepare them for employment. This study deployed the action research cycle: Identify-Plan-Act-Reflect. The pre-test results found that students had difficulties communicating confidently and interacting clearly in group discussions, and they were unable to exhibit good impression and perception during the discussions. Therefore, a teaching intervention was designed and executed to improve confidence in communicating, clarity when speaking and improvise business etiquette in a group discussion among the students. The five elements emphasized in the teaching intervention are business etiquette, pronunciation, discourse management, interactive communication and confidence. The post test results showed that the intervention has significantly improved the students’ confidence and pronunciation. This indicates that the action research study managed to enhance students’ business communication competencies.